2019
DOI: 10.1073/pnas.1816541116
|View full text |Cite
|
Sign up to set email alerts
|

Rapidly declining remarkability of temperature anomalies may obscure public perception of climate change

Abstract: The changing global climate is producing increasingly unusual weather relative to preindustrial conditions. In an absolute sense, these changing conditions constitute direct evidence of anthropogenic climate change. However, human evaluation of weather as either normal or abnormal will also be influenced by a range of factors including expectations, memory limitations, and cognitive biases. Here we show that experience of weather in recent yearsrather than longer historical periods-determines the climatic base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
87
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 154 publications
(104 citation statements)
references
References 35 publications
4
87
0
Order By: Relevance
“…An important consideration for future research is the extent to which local weather conditions or anomalous events become normalized among current and future populations. For example, there are hints that local temperature anomalies quickly become unremarkable in public discourse [106]. Such acclimatization may hinder the ability of populations to perceive the true magnitude of underlying climate trends and limit the generalizability of findings about the effect of past weather on opinion.…”
Section: Discussionmentioning
confidence: 99%
“…An important consideration for future research is the extent to which local weather conditions or anomalous events become normalized among current and future populations. For example, there are hints that local temperature anomalies quickly become unremarkable in public discourse [106]. Such acclimatization may hinder the ability of populations to perceive the true magnitude of underlying climate trends and limit the generalizability of findings about the effect of past weather on opinion.…”
Section: Discussionmentioning
confidence: 99%
“…We recognize there may be other factors affecting perceptions as well. Research suggests people only consider extreme weather remarkable if it is unusual compared to weather in recent years, and therefore they may fail to perceive climate change-induced weather that is extreme compared to historical normals (Moore et al 2019). However, extreme-weather perceptions, like temperature perceptions, often show effects from sociopolitical identity (Cutler 2015, Shao 2016b, Borick and Rabe 2017.…”
Section: Discussionmentioning
confidence: 99%
“…7 For example, a recent study that tracked remarkability of weather phenomena using social media found that the reference point for "normal" conditions is largely anchored on weather experienced within the most recent two to eight years-a period considerably shorter than the climatology community's definition of a 30-year climate normal. 8 A more rapid shift in the perceived baseline expectation of weather shifts than in actual climatological trends could help explain why fewer than half of survey respondents could correctly identify the recent warming. Winter sports participants and nonparticipants may be equally subject to shifting baseline syndrome.…”
Section: Discussionmentioning
confidence: 99%